Primary Dealers in Government Securities : Policy Issues and Selected Countries Experience - Iden, George (IMF Working Papers; Working Paper, 2003)
In many countries, authorities have designated a group of financial firms as the principal intermediaries in the government securities market-referred to as "primary dealers" or a "primary dealer system." This paper discusses policy issues related to the establishment of a primary dealer system for countries that may be considering taking this step. In this regard, a key issue is whether a primary dealer system fits into the overall strategy for financial market development in the country. Under a primary dealer system, the debt manager and the group of primary dealers pursue a common strategy in support of the effective functioning and development of primary and secondary markets for government securities. This paper presents results of a survey of country practices conducted in early 2001. Among the countries surveyed, there was broad agreement among authorities that a primary dealer system is to be highly recommended.